Cinemas and cinema-going in the United Kingdom : decades of decline, 1945–65 (2020)
Cinema-going was the most popular commercial leisure activity in the first half of the twentieth century. UK cinema attendance grew significantly in the Second World War and peaked in 1946 with 1.6 billion recorded admissions. Though ‘going to the pictures’ remained a popular pastime for the remainder of the 1940s, the transition from war to peacetime altered citizens’ leisure habits. During the 1950s, a range of factors including increased affluence, the growth of television ownership, population shifts and the diversification of leisure activities led to rapid declines in attendance. By 1965, admissions had plummeted to 327 million and the cinema held a far more marginal existence in the nation’s leisure habits. Many cinemas closed their doors and those that remained open increasingly competed with a range of venues including bingo halls, dance halls, bowling alleys, cafés and people’s homes. Cinema attendances fell in all regions, but the speed, nature and extent of this decline varied widely across the United Kingdom. By linking broad national developments to regional case studies of two similarly-sized industrial cities, Belfast and Sheffield, this book adds nuance and detail to our understanding of regional variations in film exhibition, audience habits and cinema-going experiences during a period of profound social and cultural change.